Effect of Direct Coupling on Electronic Transport and Thermoelectric Properties of Single Pyrene Molecule - Mohammed. N. Mutier; Lafy F. Al-Badry (University of Thi-Qar Journal of Science, 2021)
Electron transport characteristics through a single pyrene molecule, which connects with two metallic electrodes, are investigated by using of steady-state theoretical formalism. The transmission probability, I-V characteristics and thermoelectric properties are studied according to the influence of direct coupling between donor and acceptor. The new path between the donor and acceptor provides a direct route for the transfer of electrons between the donor and the acceptor, as well as the transfer of electrons across the molecule. We find the electronic transport properties improve by increasing donor-acceptor coupling factor.